Maternal vegetarianism and neurodevelopment of children enrolled in The Danish National Birth Cohort. (29th August 2014) - Larsen, Pernille Stemann; Nybo Andersen, Anne‐Marie; Uldall, Peter; Bech, Bodil Hammer; Olsen, Jørn; Hansen, Anne Vinkel; Strandberg‐Larsen, Katrine
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="apa12761-blkfxd-0101" position="anchor" orientation="portrait"> </boxed-text>